ANALISIS YURIDIS PEMENUHAN HAK TAHANAN MENURUT HUKUM ACARA PIDANA INDONESIA PADA DIREKTORAT TAHANAN DAN BARANG BUKTI DI POLDA MALUKU - Denny Latumaerissa (SASI, 2015)
The republic of Indonesia is a democratic law state that based on Pancasila and 1945 Constitution, that upholds human rights and guarantee every citizen is equal before the lawand government, and need to uphold the law and the government without any exception. Therefore this need to also be applied to the law enforcement, especially in the investigationphase so that the rights of offenders need to be balanced with the juridic demands (criminalcode procedure). rights of prisoners that not fully fulfilled in the Directory of Prisoners andEvidence in Maluku Police department, which there is no specific place for the prisoners tocarry out religious activities with their own beliefs they held, spiritual services that not evenlyaccessible for all prisoners (except for Christians), physical treatment that cannot be conducted because lack of gym facilities, there is no education and teaching services for the prisoners of Maluku police department, there is no polyclinic for the health check-up for sick prisoners, there is no dining hall and water is not being given, there is no separation of cell based on the level of criminality, age, and prisoners that have infectious diseases, and there is no visit room for the families and colleagues that want to visit the prisoners.